FINANCIAL INCLUSION IN INDIA: ARE WE THERE YET? - Singh, Shveta; Rohtash, (The journal of contemporary issues in business and government, 2021)
Everywhere around the world, financial inclusion has become the watchword and strategy challenge. Although money has been consistently expressed as the lifeblood of any financial system, financial inclusion is seen as an instrument that can allow inclined agencies, including low-profit groups and more vulnerable segments, to participate more fully in the financial environment. It is a structure that associates people with the formal monetary system. If individuals have simple and satisfactory access to the monetary framework, greater financial development can be achieved by that nation.This paper plans to assess the progress of financial inclusion in India from 2009 to 2018 and to prepare the Composite Financial Inclusion Index (IFI). The Wroclaw Taxonomic approach is used to create a composite financial inclusion index.